Role of integrins in angiotensin II-induced proliferation of vascular smooth muscle cells - Bunni, Marlene A. (American Physiological Society, 2011)
Angiotensin II (AII) binds to G protein-coupled receptor AT(1) and stimulates extracellular signal-regulated kinase (ERK), leading to vascular smooth muscle cells (VSMC) proliferation. Proliferation of mammalian cells is tightly regulated by adhesion to the extracellular matrix, which occurs via integrins. To study cross-talk between G protein-coupled receptor- and integrin-induced signaling, we hypothesized that integrins are involved in AII-induced proliferation of VSMC. Using Oligo GEArray and quantitative RT-PCR, we established that messages for α(1)-, α(5)-, α(V)-, and β(1)-integrins are predominant in VSMC. VSMC were cultured on plastic dishes or on plates coated with either extracellular matrix or poly-d-lysine (which promotes electrostatic cell attachment independent of integrins). AII significantly induced proliferation in VSMC grown on collagen I or fibronectin, and this effect was blocked by the ERK inhibitor PD-98059, suggesting that AII-induced proliferation requires ERK activity. VSMC grown on collagen I or on fibronectin demonstrated approximately three- and approximately sixfold increases in ERK phosphorylation after stimulation with 100 nM AII, respectively, whereas VSMC grown on poly-d-lysine demonstrated no significant ERK activation, supporting the importance of integrin-mediated adhesion. AII-induced ERK activation was reduced by >65% by synthetic peptides containing an RGD (arginine-glycine-aspartic acid) sequence that inhibit α(5)β(1)-integrin, and by ∼60% by the KTS (lysine-threonine-serine)-containing peptides specific for integrin-α(1)β(1). Furthermore, neutralizing antibody against β(1)-integrin and silencing of α(1), α(5), and β(1) expression by transfecting VSMC with short interfering RNAs resulted in decreased AII-induced ERK activation. This work demonstrates roles for specific integrins (most likely α(5)β(1) and α(1)β(1)) in AII-induced proliferation of VSMC.